Family Businesses in Transition Economies: Management, Succession and Internationalization - Dana, Leo-Paul (Springer, 2015)
​This book presents the reader a comprehensive understanding of the development of family business in transitional economies. Throughout eastern Europe, post-Communist countries transitioning to market-based economies are obtaining a variety of results due to diverse policy approaches. Expert contributions in this book draw from a wealth of information in this context and include thought-provoking policy prescriptions for the future. This book concentrates on the challenges to predict the direction emerging markets will take, particularly when dealing with the wide-ranging social and economic situations taking place in post-Communist Eastern Europe. This reference volume for policymakers, educators, investors, and researchers also provides a much-needed and timely survey of family firms in the transitioning markets of post-Communist Europe.